Structural Design of Handicrafts Based on Dynamic Simulation Technology - Kun Meng; Fulong Liu (Advances in Multimedia)
In order to improve the effect of handicraft structure design, this study combines the dynamic simulation technology to build a handicraft structure design system and transmits data through dynamic simulation signals to improve the effectiveness of the interactive design of artworks. In order to provide a simpler and faster development process for interactive media applications, this study develops an interactive media art design system with a node-based visual programming model as the core processing logic. The digital Gaussian shaping method based on the programmable logic device can not only realize real-time Gaussian shaping of the nuclear pulse signal but also meet the needs of later function expansion, maintenance, and upgrade of the system. In addition, this study verifies the effectiveness of the handicraft structure design system based on dynamic simulation technology through the analysis of multiple sets of simulation data.